Komputerisasi Pendataan Presensi pada SMK Sasmita Jaya 2 Pamulang dengan Metode Prototype - Pandu Dewonoto Laut Santoso; Indah Riski; Aries Saifudin; Sri Mulyati (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Attendance data collection can be said to be a very crucial activity because with all information about the presence of students at an educational institution can make it easier for teachers in the decision-making stage during the assessment process for students, but the attendance data collection which is carried out conventionally is actually faced with various kinds of problems that where some of them are the amount of time required in conventional attendance data collection and the high risk of damage to the attendance data sheet that applies paper as the main medium. Based on these problems, computerization of the attendance data collection process is deemed necessary. The attendance data collection system developed using the prototype. By using this prototype method, the main functions of the system will be developed first. If it is correct, then proceed with the other supporting parts. The attendance data collection system developed can be an appropriate system in solving all kinds of problems encountered in conventional attendance data collection activities. And to meet the satisfaction criteria from the user side, which in this context are the teachers at SMK Sasmita Jaya 2 Pamulang.